Comparative Analysis of Estimation Methods of the Physiological Signals Variability - Orikhovska, K.B.; Fainzilberg, L.S. (Кибернетика и вычислительная техника, 2017)
The purpose of the article is further development and experimental research of methods for analyzing the variability of physiological signals under external influences on the body.